Factors affecting employment issues related to Indonesian workers in Sabah: a case study of Mensuli estate / Nur Aziemah Jasni and Nasuddin Othman - Jasni, Nur Aziemah; Othman, Nasuddin (2016)
The study analysed the employment issues related to Indonesian workers in Sabah. This study aims to determine the main factors that contribute to the oil palm productivity in relation to minimum wage, welfare management, and training provided to the Indonesian workers, to examine productivity status of the foreign harvesters and loose fruit collectors with welfare management and to examine the foreign harvesters’ and loose fruit collectors’ employment situations in oil palm plantations in Mensuli Estate. The method that had been used to obtain the data in this study was questionnaires distribution method and personal interviews. The data was analysed by using factorial analysis. The factor analysis identified seven factors that led to employment issues of Indonesian workers. The factors including competition with Indonesian palm oil plantation, training provided by the company, welfare management, satisfaction with the company welfare management, wage satisfaction, minimum wage and high cost of living. It was found that most of the respondents knew about the wage hike in Indonesia palm oil plantations and they were willing to return back to their homeland. Therefore the government should take an action to prevent the workers shortage issues in the plantation by encouraging local younger generation to work in the plantation sectors.